Upaya Badan Narkotika Nasional Dalam Penanggulangan Bahaya Penyalahgunaan Narkoba Bagi Remaja Di Kota Lhokseumawe Dengan Pendidikan Islam - Abd Mukti; Zulkarnain Nasution; Saiful Bahri (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Seeing the development of teenagers in the city of Lhokseumawe is now very alarming with the number of cases of drug abuse that are increasingly disturbing parents, even the abuse of shabu-shabu, marijuana and buying glue to inhale which is bought freely, therefore this research wants to examine in more depth, How to Efforts Lhokseumawe City National Narcotics Agency in Overcoming the dangers of drug abuse for adolescents in Lhokseumawe City, the type of research used is qualitative research with a phenomenological approach and data collection techniques through observation, interviews and documentation. The results obtained in this research, BNN has carried out prevention efforts through prevention, namely the dissemination of information through banners, billboards, banners, as well as counseling to villages with the Gampong Shine (Clean Narcotics) program. urine test, interactive dialogue through RRI radio, BNN greets (gampong tour program), both prevention through community empowerment, namely holding training and coaching as well as workshops on family resilience such as sewing training for young women and mothers, catfish cultivation for teenagers and gentlemen, thus the results obtained are that the Lhokseumawe City BNN has made maximum efforts in the form of prevention